Effects of Animosity and Allocentrism toward Consumer Ethnocentrism in Shaping Consumers’ Willingness to Purchase: A Case Study on Consumers in Greater Jakarta (Jabodetabek Area) in Purchasing Malaysian Products - Selli, Maeyta; Kurniawan, Heri (ASEAN Marketing Journal, 2021)
This paper aims to: (1) specify factors mediating the effects of consumer animosity towards the consumers’ willingness to purchase imported products; (2) specify factors mediating the effects of allocentrism towards consumers’ willingness to purchase imported product; and (3) examine whetherproduct quality comparison between domestic vis-à-vis imported products moderates the relationships between: (a) consumer animosity and consumers’ willingness to purchase (b)ethnocentrism and consumers’ willingness to purchase. A survey was conducted to 209 respondents that have boughtMalaysian products in the past three months and lived in Jabodetabek (Jakarta, Bogor, Depok, and Bekasi) area. The result shows that ethnocentrism mediated the relationship between animosity and consumers’ willingness to purchase; while it does not work as a mediator in the relationship betweenallocentrism and consumers’ willingness to purchase. In addition, product quality comparison does not moderate the relationship between animosity and consumers’ willingness to purchase as well as ethnocentrism and consumers’ willingness to purchase. Interpretations, contributions, and implicationsfor manager are also discussed.